Love without limits : Jesus' radical vision for love with no exceptions - Bussie, Jacqueline Aileen (Fortress Press, 2018)
How can we overthrow hate and heal hurt in today's divided world? According to Jacqueline A. Bussie, by learning to love as God does--without limits or exceptions. In Love Without Limits, Bussie imparts practical solutions for people who yearn to love across difference. Through poignant memoir, engaging theological reflection, inspiring stories of friendship, creative readings of scripture, and shout-outs to some of love's unsung heroes, Bussie challenges readers to answer God's call to practice a love so vast that it excludes no one.